Talking is for all how children and teenagers develop emotional literacy - Rudd, Betty K.; Rudd, Betty K.; Rudd, Betty K.; Rudd, Betty K.; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2008)
Betty Rudd presents a resource for all those wanting to provide a comprehensive and unified programme to assist children and adolescents in their emotional development.
"A Lucky Duck book".
Originally published: in 3 v. as Talking is for kids - Talking is for us - Talking is for teens.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Emotional intelligence; Emotions in children; Emotions in adolescence; Interpersonal communication; Electronic books